Activated bentonite nanocomposite for the synthesis of solketal from glycerol in the liquid phase - Pérez, Federico Martín (2022)
Activated bentonites are low-cost acid catalysts used in several reactions. However, their application at an industrial scale is affected by the formation of colloidal suspensions when these bentonites are in aqueous solutions. In order to overcome these limitations, this work proposes obtaining a catalyst based on a composite containing natural bentonite within a silica–resin structure, which allows separating and re-utilizing the catalyst more easily and without centrifugal filtration requirements. By means of characterization techniques, the present study determined that the activated bentonite composite presented a total specific surface area of ~360 m² g⁻¹, ~4 mmol of acid sites per gram of bentonite, and sites with strong acid strength, all of which bestowed activity and selectivity in the solketal synthesis reaction from glycerol and acetone, reaching equilibrium conversion within a short reaction time. Furthermore, the present work developed a Langmuir– Hinshelwood–Hougen–Watson kinetic model, achieving an activation energy of 50.3 x 3.6 kJ mol⁻¹ and a pre-exponential factor of 6.4 x 106 mol g ⁻¹ L⁻¹ s⁻¹, which are necessary for reactor design.